Sustaining quality academic programme for globally marketable graduates / Wardah Tahir ... [et al.] - Tahir, Wardah; Seman, Noraini; Ariffin, Suriyani; Samat, Muhammad Faizal; Jaafar, Jurina; Abd Jamil, Azhar; Sapien, Norita (2023)
Universiti Teknologi MARA (UiTM) has expanded from an institute to a mega university that offers innovative education with state-of-the-art infrastructure and technology. UiTM provides more than 500 academic programmes at its 34 campuses, 4 colleges of studies, 13 faculties, and 9 academic centres nationwide. It continues to broaden access to higher education, contributing to nation-building by producing professionals and shaping the future. The university has the largest number of academic programmes in the country, covering comprehensively most disciplines. This paper examines the competitiveness of academic programmes, including their popularity, enrolment, and graduate employability. In the evaluation of the programme, an assessment tool named IDSPA (Indeks Daya Saing Program Akademik) is utilised. According to the results of the IDSPA analysis, most of the academic programmes are well-maintained, with some requiring curriculum revision. Some programmes require rebranding, while others may be discontinued. How does an institution ensure that its academic programmes are relevant, competitive, and viable? A framework of integrated academic programme sustainability maintenance is proposed to capture the key components in ensuring the viability of an academic programme.